Etika Kepedulian dalam Perubahan Iklim dan Tanggung Jawab Moral Terhadap Generasi Masa Depan - Ainia, Dela Khoirul (HUMANIKA, 2025)
Research related to the ethics of care in climate change and moral responsibility towards future generations aims to explore the role of ethics of care in climate change and moral responsibility towards future generations. The method used in this research is descriptively qualitative and was obtained through data collection from online news media and article reviews. The analysis in this study is descriptively interpretative. The study was carried out in three stages: reduction, data presentation, and verification. The results showed that the ethics of care play an important role in life and can be used as a guide for human behavior to respect and preserve nature, as nature has provided human life support. Humans and nature cannot be separated, so they are interrelated. Humans have a moral responsibility towards nature because they will impact the sustainability of human life. The current climate problem is a serious problem that needs to be solved immediately, namely by building awareness of the application of the ethics of care, as humans care for fellow humans as well as the universe. The phenomenon of climate change is rooted in human activities that are less wise in managing nature. Thus, human moral responsibility is not only carried out individually but also becomes a collective responsibility involving individuals, governments, companies, NGOs, and other groups involved in managing nature. Therefore, there needs to be conscious collaboration in managing nature because this awareness has an impact on the lives of future generations.